Immune Reconstitution Inflammatory Syndrome as a Posttransplantation Complication in Primary Immunodeficiency With Disseminated Mycobacterium avium. (12th June 2019) - Manion, Maura; Dimitrova, Dimana; Pei, Luxin; Gea-Banacloche, Juan; Zelazny, Adrian; Lisco, Andrea; Zerbe, Christa; Freeman, Alexandra F; Holland, Steven M; Kanakry, Christopher G; Kanakry, Jennifer A; Sereti, Irini
Abstract: Patients with primary immunodeficiencies undergoing allogeneic hematopoietic cell transplantation (HCT) for difficult-to-control infections can experience immune reconstitution inflammatory syndrome (IRIS) following engraftment. In 3 patients with post-HCT IRIS related to mycobacterial infection, in vitro data demonstrate the emergence of pathogen-specific immune responses and a concomitant rise in plasma inflammatory markers.